2019
DOI: 10.1111/eth.12859
|View full text |Cite
|
Sign up to set email alerts
|

Prey colour biases in jumping spiders (Habronattus brunneus) differ across populations

Abstract: Predators often avoid aposematic prey as a result of aversions to particular prey signals (e.g., bright colours and noxious odours). These aversions may be flexible, that is, they can be reinforced or extinguished with experience. As such, we might expect populations to differ in their biases against certain prey characteristics (e.g., colour or pattern) depending on the prey available in the community. Here, we tested whether the jumping spider, Habronattus brunneus(Salticidae), exhibits colour biases against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…If paint spread beyond the abdomen (e.g., onto the legs or thorax), the termite was discarded. Previous studies revealed no significant differences in movement rates between unpainted and painted termites [23,24] suggesting that this color manipulation does not inhibit their natural movement rates.…”
Section: Experimental Set 1: Db-induced Unpalatability In Termitesmentioning
confidence: 75%
See 2 more Smart Citations
“…If paint spread beyond the abdomen (e.g., onto the legs or thorax), the termite was discarded. Previous studies revealed no significant differences in movement rates between unpainted and painted termites [23,24] suggesting that this color manipulation does not inhibit their natural movement rates.…”
Section: Experimental Set 1: Db-induced Unpalatability In Termitesmentioning
confidence: 75%
“…Because the DB solution is colorless, we needed a way to keep track of which termites in each experiment were DB-treated and which were controls. To do this, we randomly assigned each termite a particular color using a previously published method of termite color manipulation that uses flat oil-based enamel paints (Testors, Rockford, IL, USA) [23,24]. In this study, we were not interested in the spiders' color preferences per se, and so we strategically chose two colors that we expected to be neutral to the spiders and that they would readily attack: green (product #1164TT) and brown (product #1166TT).…”
Section: Experimental Set 1: Db-induced Unpalatability In Termitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been shown that many predators are very conservative in their prey preferences, and avoid brightly colored prey even when they are edible [33]. Nonetheless, finding evidence for innate aversion of captive adult spiders to wasps with the BOB coloration does not rule out the possibility that learning is important in this predator prey interaction; indeed, aversions to particular prey colors can change with experience [38]. We found that spiders from natural conditions showed increased aversion over time, and this aversion coincides with the toxicity analyses and the aposematic pattern of the wasps.…”
Section: Predator Responses Towards Bob Waspsmentioning
confidence: 99%
“…Like other jumping spiders, Habronattus are voracious predators 25 with exceptional visual acuity in their large forward-facing principal eyes 26 . Recent work suggests that spiders in this genus likely have the ability to distinguish a wide range of colors from UV to red 27 and behavioral work suggests that they attend to both color and odor cues while foraging 18 20 , 24 . They are common in a variety of habitat types 28 where they likely encounter potential insect prey with combinations of defensive odors and colors.…”
Section: Introductionmentioning
confidence: 99%